BONUM COMMUNE DALAM CARA HIDUP MASYARAKAT JAWA: HIBRIDITAS PERTEMUAN BUDAYA JAWA AREK - Autar Abdillah (Arete, 2019)
This article intends to reveal that the common good in the Javanese Arekculture was born from various mixtures (hybridities) of cultural encounters over avery long period of time and made Javanese Arek culture one of the most import-antculturesincreatingdiversity.TheearlydaysoftheformationofJavaneseArekcultureinthe4-9centuryADwerebuildingsofHindu-Javanese nobility,followedbyameetingoftradersandtheentryofIslam,Mataram,Colonialism,Christianity,andModernization. 111The human character and the Javanese Arek cultural community are alsoformed from harsh natural pressures, such as the eruption of Mount Kelud duringthe year 1037-1468 or for 431 years with 22 eruptions, thus covering up the aris-tocracysurroundingthesmallislandsintheJavaneseArekculturalarea.